2014
DOI: 10.1080/09640568.2014.938803
|View full text |Cite
|
Sign up to set email alerts
|

Beer, beef, and boards: the role of intermediaries in payment for ecosystem services arrangements in northwestern Montana

Abstract: Payments for ecosystem or ecological services (PES) are voluntary, often marketbased approaches to protecting environmental values. In the rural United States, some landowners receive PES through government led conservation programs, but little is known about their involvement in market based arrangements. We analyzed three examples of market based PES arrangements in northwestern Montana: watershed restoration and craft brewing, niche meat production, and certified timber supplies. We find that intermediaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…However, discussions of PES arrangement in general, and REDD+ literature in particular, have tended to focus on targeting buyers and providers in isolation, while overlooking the important functions of intermediaries (Davis et al, 2014. In this paper, we have examined the necessary roles of intermediaries in REDD + projects.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, discussions of PES arrangement in general, and REDD+ literature in particular, have tended to focus on targeting buyers and providers in isolation, while overlooking the important functions of intermediaries (Davis et al, 2014. In this paper, we have examined the necessary roles of intermediaries in REDD + projects.…”
Section: Discussionmentioning
confidence: 98%
“…To assume this more transformative function, they must develop specific strategies to bring together (network) local actors for REDD + project design, align the interests and demands of different local actors to redevelop their relations for shared goals, and translate those goals to fit into the national and international agenda of carbon stock improvement. All of these roles have been shown to be critical for effective intermediaries in PES arrangements (Davis et al, 2014. While ecosystem services, such as carbon sequestration and biodiversity, have global implications, they are often viewed as abstract notions by local communities and other stakeholders.…”
Section: Building Effective Redd+ Intermediariesmentioning
confidence: 99%
See 2 more Smart Citations
“…A diversity of organisations, governmental and non-governmental, have facilitated development and operation of PES schemes (Porras et al, 2008), but Trust Funds and local and international NGOs are observed to be the most common forms of intermediary. The private sector has not generally provided the intermediary function, though Davis et al (2015), cite exceptions from northwest Montana, USA.…”
Section: Assessment Of Intermediary Roles In Pes Schemesmentioning
confidence: 99%